2021
DOI: 10.5194/acp-21-11437-2021
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric gaseous hydrochloric and hydrobromic acid in urban Beijing, China: detection, source identification and potential atmospheric impacts

Abstract: Abstract. Gaseous hydrochloric (HCl) and hydrobromic acid (HBr) are vital halogen species that play essential roles in tropospheric physicochemical processes. Yet, the majority of the current studies on these halogen species were conducted in marine or coastal areas. Detection and source identification of HCl and HBr in inland urban areas remain scarce, thus limiting the full understanding of halogen chemistry and potential atmospheric impacts in the environments with limited influence from the marine sources.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…As to Br y , BrCl is also the most abundant species which contributes ∼60%, whereas HOBr and Br 2 take up ∼20%. Our simulated halogen species are in line with the available observational reports of reactive bromine species in China by Peng et al and Fan et al and also within the ranges in previous studies of chlorine species in China. ,, …”
Section: Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As to Br y , BrCl is also the most abundant species which contributes ∼60%, whereas HOBr and Br 2 take up ∼20%. Our simulated halogen species are in line with the available observational reports of reactive bromine species in China by Peng et al and Fan et al and also within the ranges in previous studies of chlorine species in China. ,, …”
Section: Results and Discussionsupporting
confidence: 92%
“…In the past few years, observational studies have reported elevated levels of halogen species in China. The majority of these reports focused on ClNO 2 and a few on Cl 2 , and bromine species (BrCl, HOBr, Br 2 , and HBr). , A few modeling studies evaluated the impacts of chlorine chemistry on O 3 and PM 2.5 . , However, the overall impact of anthropogenic halogens (particularly bromine) on aerosols and haze pollution in China remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…There, reaction with NO x and VOCs plays a more substantial role, as in the following simplified mechanism XO + NO 2 + normalM XONO 2 + normalM XONO 2 + normalH 2 normalO ( aq ) HOX or X 2 + HNO 3 normalX + RH O 2 RO 2 + HX where X represents a halogen atom. One prevalent mechanism in the midlatitudes is the conversion of N 2 O 5 to ClNO 2 on the surface of chloride-containing aerosol. Transport of halogen reservoirs such as ClNO 2 , which may also be formed by the reaction of Cl radicals with NO 2 , has implications for the downwind oxidizing capacity of the troposphere, , and several recent studies have demonstrated the impact of gas-phase halogen species on urban air quality via reactions with NO x and VOCs. Halogens also convert elemental mercury to oxidized mercury , and dimethyl sulfide to sulfate .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to oxidation chemistry driven by ozone (O 3 ), hydroxyl radicals (OH), and nitrate radicals (NO 3 ), chlorine radical (Cl) chemistry has been shown to substantially contribute to the atmospheric degradation of anthropogenic emissions, , inorganic aerosol formation, and secondary organic aerosol formation (SOA) . These impacts have been the strongest during wintertime in polluted urban environments, , likely due to increased combustion activities, increased biomass burning, and lowered boundary layer heights contributing to increased concentrations. Under typical ambient conditions, Cl concentrations are thought to range from 10 2 to 10 5 molecules cm –3 , one or several orders of magnitude lower than concentrations of the OH radical, 10 6 molecules cm –3 .…”
Section: Introductionmentioning
confidence: 99%